A Current Concept Review for the Use of External Fixators in Elderly Patients with Intertrochanteric Fracture - Alireza Moharrami; Mir Mansour Moazen Jamshidi; Soroush Alaeddini; Mazaher Ebrahimian; Amir Reza Mafi (Journal of Orthopedic and Spine Trauma, 2023)
Intertrochanteric (IT) fractures are responsible for almost half of the fractures in the elderly. The financial burdens of IT fractures are considerable, not only because of their influence on morbidity and mortality but also because they might lead to functional limitation, alleviated quality of life, and a limited possibility to work. There are several methods of fixations for IT fractures, such as cephalomedullary nailing, dynamic hip screw (DHS), proximal femur plate, and external fixator. Most of the patients with this fracture were unsuitable for anesthesia and surgical procedure. The external fixator is a fast, non-invasive, and bloodless method for fixation which would be performed with light sedation. In the present study, we reviewed recent literature regarding external fixators for IT fractures.